2021
DOI: 10.2174/1386207323666201110152615
|View full text |Cite
|
Sign up to set email alerts
|

Tinocordiside from Tinospora cordifolia (Giloy) May Curb SARS-CoV-2 Contagion by Disrupting the Electrostatic Interactions between Host ACE2 and Viral S-Protein Receptor Binding Domain

Abstract: Background: SARS-CoV-2 has been shown to bind the host cell ACE2 receptor through its spike protein receptor binding domain (RBD), required for its entry into the host cells. Objective: We have screened phytocompounds from a medicinal herb, Tinospora cordifolia, for their capacities to interrupt the viral RBD and host ACE2 interactions. Method: We employed molecular docking to screen phytocompounds in T. cordifolia against the ACE2-RBD complex, performed molecular dynamics (MD) simulation, and estimated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The main aim of this study was to evaluate the potential of Ayurvedic medicines against COVID-19 infection. The premise for this study has been recognition of epidemic in Ayurveda, mention of treatments for ailments with symptoms resembling those of mild to moderate cases of COVID-19 and reports on anti-viral, immune-modulatory and anti-inflammatory effects of the Ayurvedic medicines being studied or their individual constituents ( Balkrishna et al, 2021b , 2020b , 2020a ; Choudhury et al, 2014 ; Gautam et al, 2009 ; Gupta et al, 2011 ; Hagenlocher et al, 2013 ; Kamala et al, 2018 ; Kanwar and Bhutani, 2010 ; Lee et al, 2019 ; Mahajan et al, 2013 ; Majdalawieh and Carr, 2010 ; Nicolis et al, 2009 ; Pattanayak et al, 2010 ; Pynam and Dharmesh, 2018 ; Rajaram et al, 2018 ; Sinha et al, 2004 ; Tiwari et al, 2017 ; Yadav et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim of this study was to evaluate the potential of Ayurvedic medicines against COVID-19 infection. The premise for this study has been recognition of epidemic in Ayurveda, mention of treatments for ailments with symptoms resembling those of mild to moderate cases of COVID-19 and reports on anti-viral, immune-modulatory and anti-inflammatory effects of the Ayurvedic medicines being studied or their individual constituents ( Balkrishna et al, 2021b , 2020b , 2020a ; Choudhury et al, 2014 ; Gautam et al, 2009 ; Gupta et al, 2011 ; Hagenlocher et al, 2013 ; Kamala et al, 2018 ; Kanwar and Bhutani, 2010 ; Lee et al, 2019 ; Mahajan et al, 2013 ; Majdalawieh and Carr, 2010 ; Nicolis et al, 2009 ; Pattanayak et al, 2010 ; Pynam and Dharmesh, 2018 ; Rajaram et al, 2018 ; Sinha et al, 2004 ; Tiwari et al, 2017 ; Yadav et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 causes viraemia after entering the body and the main clinical manifestations are fever, pharyngalgia, fatigue, diarrhea and other non-specific symptoms. The phytochemicals present in the Ayurvedic medicines mentioned here work at different steps of viraemia, such as, to prevent viral entry ( Balkrishna et al, 2021b , 2020a ), to inhibit viral replication (unpublished data), and to reduce inflammation of the respiratory tract and strengthen immunity ( Balkrishna et al, 2020b ). Observations from a randomized placebo controlled pilot clinical study, that evaluated the effectivity of these medicines on a slightly larger asymptomatic to mildly symptomatic patient pool, upholds our findings from this study ( Devpura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 Tinocordiside from Tinospora cordifolia reduced the free binding energy of the host cell ACE-2 and the SARS-CoV-2 spike protein’s Receptor Binding Domain. 40 Other studies identified the potential use of several phyto-compounds such as diterpene, tetranortriterpenoid, phytosterols, and several other FDA approved compounds for efficient blocking of the major protease, Nsp9 replicase, and spike proteins of the SARS-CoV-2 virus. 41 , 42 The various bioactive compounds present in Withania somnifera (Ashwagandha), such as Withanone, Withanoside X, Ashwagandanolide, Dihydrowithaferin A, and Withanolide N were identified as potent inhibitors to the entry of the virus into the host cell using docking experiments in-silico.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the screened chemical constituents, molecular docking along with molecular dynamics studies revealed that berberine regulates the M pro protein function and thus inhibits the viral replication [82]. Furthermore, a study by Balkrishna et al demonstrated that one of the phytocompounds of T. cordifolia "Tinocordiside" significantly reduced the electrostatic interaction between ACE2-RBD complexes that leads to enhancement in the flexibility of the complex [83]. Thus, we can postulate that Tinocordiside could be one of the viable options for controlling the SARS-CoV-2 entry into the host cell.…”
Section: Tinospora Cordifolia (Guduchi)mentioning
confidence: 99%